The use of hyperbaric oxygen for veterans with PTSD: basic physiology and current available clinical data - Doenyas-Barak, Keren; Kutz, Ilan; Lang, Erez; Merzbach, Rachel; Lev Wiesel, Rachel; Boussi-Gross, Rahav; Efrati, Shai (Frontiers in Neuroscience, 2023)
Post-traumatic stress disorder (PTSD) affects up to 30% of veterans returning from the combat zone. Unfortunately, a substantial proportion of them do not remit with the current available treatments and thus continue to experience long-term social, behavioral, and occupational dysfunction. Accumulating data implies that the long-standing unremitting symptoms are related to changes in brain activity and structure, mainly disruption in the frontolimbic circuit. Hence, repair of brain structure and restoration of function could be a potential aim of effective treatment. Hyperbaric oxygen therapy (HBOT) has been effective in treating disruptions of brain structure and functions such as stroke, traumatic brain injury, and fibromyalgia even years after the acute insult. These favorable HBOT brain effects may be related to recent protocols that emphasize frequent fluctuations in oxygen concentrations, which in turn contribute to gene expression alterations and metabolic changes that induce neuronal stem cell proliferation, mitochondrial multiplication, angiogenesis, and regulation of the inflammatory cascade. Recently, clinical findings have also demonstrated the beneficial effect of HBOT on veterans with treatment-resistant PTSD. Moderation of intrusive symptoms, avoidance, mood and cognitive symptoms, and hyperarousal were correlated with improved brain function and with diffusion tensor imaging-defined structural changes. This article reviews the current data on the regenerative biological effects of HBOT, and the ongoing research of its use for veterans with PTSD.